Serum IgE levels are associated with coronary artery disease severity. (August 2016) - Guo, Xiaoxiao; Yuan, Su; Liu, Yongtai; Zeng, Yong; Xie, Hongzhi; Liu, Zhenyu; Zhang, Shuyang; Fang, Quan; Wang, Jing; Shen, Zhujun
Abstract: Background and aims: Immunoglobulin E (IgE), a key element of allergic reactions, was considered to be involved in the development of atherosclerosis and the pathogenesis of myocardial ischemia. This study was designed to test whether total serum IgE levels were associated with the atherosclerosis severity of coronary artery disease (CAD). Methods: Total serum IgE concentrations were measured in 708 consecutive patients who were presented to our center for coronary angiography. Atherosclerosis severity of CAD was assessed by the number of diseased vessels showing ≥50% diameter stenosis and quantified by Gensini score. Results: Patients with CAD (N = 562) had higher serum IgE levels than those without CAD (N = 146) [55.90 (19.10–156.00) vs. 26.90 (11.80–62.10) KU/L, p = 0.003]. Furthermore, the serum IgE levels were significantly increased in patients with multivessel disease (MVD) compared to those with single-vessel disease [61.80 (23.20–159.00) vs. 32.45(14.15–94.38) KU/L, p = 0.003]. After adjustment for traditional cardiovascular risk factors, a high serum IgE level was an independent predictor for an increased risk of MVD (OR 1.003; 95% CI 1.001–1.004; p = 0.041). Receiver-operating characteristic curve analysis demonstrated that serum IgE levels improved the predictive capability of traditional risk factors for MVD (area under the curve with and without IgE: 0.734 and 0.713, respectively, p < 0.001). Meanwhile, there was a significant linear relationship between Gensini score and the serum IgE level quartiles ( p for linear trend <0.001). Conclusions: Increased total serum IgE levels are associated with MVD and contribute to discriminating CAD severity independently of traditional cardiovascular risk factors. Highlights: Serum IgE levels are positively associated with the severity of coronary artery disease (CAD). A high serum IgE level is an independent predictor for an increased risk of multivessel disease (MVD). Serum IgE levels may improve the predictive capability of traditional risk factors for MVD in CAD patients.